Activation of carbon suboxide (C3O2) by U(III) to form a cyclobutane-1,3-dione ring - Tsoureas, Nikolaos; Cloke, F. Geoffrey N. (Chemical Communications, 2018)
The activation of C3O2 by the U(iii) complex [U(η5-Cp′)3] (Cp′ = C5H4SiMe3) is described. The reaction results in the reductive coupling of three C3O2 units to form a tetranuclear complex with a central cyclobutane-1,3-dione ring, with concomitant loss of CO. Careful control of reaction conditions has allowed the trapping of an intermediate, a dimeric bridging ketene complex, which undergoes insertion of C3O2 to form the final product.